Formation of 1, 3‐Diphosphacyclobutadiene Complexes from Phosphaalkynes and Their Coordination Behavior (Eur. J. Inorg. Chem. 10/2014). Issue 10 (April 2014) - Rummel, Eva‐Maria; Eckhardt, Maria; Bodensteiner, Michael; Peresypkina, Eugenia V.; Kremer, Werner; Gröger, Christian; Scheer, Manfred
Abstract : The cover picture shows organometallic and inorganic building blocks being combined to form unprecedented new species. Discrete molecules or polymeric compounds (depending on the stoichiometry) are formed in the solid state. Spectroscopic evidence suggests the fragmentation of the polymeric species in solution. Sometimes recombination leads to different coordination polymers, which are a major research interest of the Scheer group. Details are discussed in the article by M. Scheer et al. onp. 1625 ff . For more on the story behind the cover research, see theCover Profile .